Impact of canopy management practices on phenolic composition and sensory profile of cv. Teran wine - Bubola Marijan; Sivilotti Paolo; Rossi Sara; Bestulić Ena; Plavša Tomislav; Radeka Sanja (BIO Web of Conferences, 2022)
The aim of this study was to investigate the impact of early leaf removal (ELR) and cluster thinning (CT) on the phenolic composition of cv. Teran berries and wines, and the sensory profile of wines at 6 and 24 months after fermentation. Although only ELR increased the concentration of total anthocyanins in the berries as compared to the untreated control (UC), both ELR and CT had higher concentration of total anthocyanins and greater colour intensity in the resultant wines than the UC. Similar effects were obtained with total phenolics in the berries and the wines; while CT obtained higher concentration of total phenolics in the berries than UC only in one season, same treatment obtained higher concentration of total phenolics in the wine in both seasons as compared to UC. Only minor sensory differences in wines were obtained at the age of 6 months, while treatments were highly discriminated 24 months after fermentation, when both ELR and CT wines had more enhanced fruitiness, aromatic intensity, complexity, body, balance and wine overall quality than UC. The obtained results indicate that adequate wine aging period is needed for a relevant assessment of the impact of vineyard management practices on wine sensory characteristics.